Treatment of a Subacute Locked Thumb Metacarpophalangeal Joint with Sesamoid Entrapment - Carroll, John J. (Case Rep Orthop, 2019)
INTRODUCTION: Locked thumb metacarpophalangeal (MCP) joints due to entrapped radial sesamoids are rare injuries that commonly require open reduction, especially when the injury is delayed in presentation. CASE PRESENTATION: We present a case of a 24-year-old female with a subacute thumb MCP joint subluxation due to an incarcerated radial sesamoid. She underwent successful closed reduction but had persistent pain and difficulty gripping large objects necessitating eventual open volar plate repair despite therapy. She was able to achieve full motion, with little pain and disability, after undergoing delayed volar plate repair. DISCUSSION: Delayed volar plate repair may be considered for those patients who fail to improve with conservative management and occupational therapy after a successful closed reduction for thumb MCP joint subluxation due to an incarcerated radial sesamoid.